2009
DOI: 10.1093/jxb/erp062
|View full text |Cite
|
Sign up to set email alerts
|

Crops and climate change: progress, trends, and challenges in simulating impacts and informing adaptation

Abstract: Assessments of the relationships between crop productivity and climate change rely upon a combination of modelling and measurement. As part of this review, this relationship is discussed in the context of crop and climate simulation. Methods for linking these two types of models are reviewed, with a primary focus on large-area crop modelling techniques. Recent progress in simulating the impacts of climate change on crops is presented, and the application of these methods to the exploration of adaptation option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
217
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(228 citation statements)
references
References 126 publications
5
217
0
6
Order By: Relevance
“…A widely applied approach to estimating climate change impact on crop yield is crop simulation modeling (e.g., Lin et al, 2005;Liu et al, 2010;Tao et al, 2009;Xiong et al, 2012;Xiong et al, 2007;Zhang et al, 2013), where key socio-economic factors other than climate variables in crop production are typically out of consideration (Challinor et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A widely applied approach to estimating climate change impact on crop yield is crop simulation modeling (e.g., Lin et al, 2005;Liu et al, 2010;Tao et al, 2009;Xiong et al, 2012;Xiong et al, 2007;Zhang et al, 2013), where key socio-economic factors other than climate variables in crop production are typically out of consideration (Challinor et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…We found that the genomic architecture of flowering time has been shaped by the most recent whole-genome duplication, which suggests that ancient paralogues can remain in the same regulatory networks for dozens of millions of years. This genome represents a cornerstone for future research programs aiming to exploit genetic diversity to improve biotic and abiotic stress resistance and oil production, while also considering agricultural constraints and human nutritional needs 8,9 .…”
mentioning
confidence: 99%
“…Downscaling is necessary for agricultural impacts assessments because factors that affect crops (soil, surface, and farming practices) vary at finer scales than typical GCM spatial resolution (>100 km) (10,11). Some of the earliest downscaling approaches used observed relationships between mesoscale and local climate variables to relate GCM output to local climate (12).…”
mentioning
confidence: 99%